1999
DOI: 10.1021/ci9800413
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Structure−Activity Relationship (QSAR) and Receptor Mapping of Cytochrome P-45014αDM Inhibiting Azole Antifungal Agents

Abstract: Molecular modeling was performed by a combined use of conformational analysis and 3D-QSAR methods to distinguish structural attributes common to a series of azole antifungal agents. Apex-3D program was used to recognize the common biophoric structural patterns of 13 diverse sets of azole antifungal compounds demonstrating different magnitudes of biological activity. Apex-3D identified three common biophoric features significant for activity: N1 atom of azole ring, the aromatic ring centroid 1, and aromatic rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Unfortunately the predictions based on docking analysis in this model could not be confirmed by X-ray crystallography [ 139 ]. Furthermore a three-dimensional quantitative structure-activity model has been described [ 140 ].…”
Section: Mode Of Actionmentioning
confidence: 99%
“…Unfortunately the predictions based on docking analysis in this model could not be confirmed by X-ray crystallography [ 139 ]. Furthermore a three-dimensional quantitative structure-activity model has been described [ 140 ].…”
Section: Mode Of Actionmentioning
confidence: 99%
“…The piperazine rings have chair conformations, and the benzene ring is distorted because three atoms of the ring are split on the basis of their thermal parameters [55,56] . Phenylpiperazine ring has no contribution to interact with the heme group CYP51, it interacts with amino acid residues in the substrate access channel [68–73] . The anisotropy and span of the carbon nuclei on the phenylpiperazine ring are low.…”
Section: Resultsmentioning
confidence: 99%
“…5 Indeed, several three-dimensional quantitative structure-activity relationship studies (3D QSAR) have been reported for different datasets of azole derivatives 2,6,[9][10][11][12] however, this strategy afforded models with moderate robustness and local predictive ability only. For instance, Di Santo and co-workers 1 report that their CoMFA model was contradicted by the synthesis and evaluation of novel compounds.…”
Section: Ketoconazole Nystatin Caspofugin Naftifinementioning
confidence: 99%
“…6,7 Nevertheless, some antifungal drugs are either highly toxic (e.g., amphotericin B, AMB) or becoming ineffective against resistant strains that affect mostly hospitalized patients (e.g., flucytosine and azoles). 3 In fact, azole resistance is a major concern in long-course treatment of AIDS patients.…”
mentioning
confidence: 99%